UJI KELAYAKAN SISTEM PEMBELAJARAN TERPADU (SIPANTER) BERBASIS MOODLE - Syamsul Bahri; Mitra Rahayu; Merta Simbolon (Universitas Sultan Ageng Tirtayasa, 2021)
Moodle-based Learning System Development or sistem pembelajaran terpadu (SiPanTer) aims to determine the feasibility of e-learning being developed. The feasibility of e-learning is based on expert validation results, namely information and communication engineering experts. The research and development model used is the Borg and Gall model adapted by Sugyono. The research and development stage consists of 10 steps, namely 1) analysis of potential and problems; 2) data collection; 3) product design; 4) design validation; 5) design revision; 6) product trials; 7) product revision; 8) trial use; 9) product revision; and 10) products. The data collection technique was carried out using expert validation sheets and teacher and lecturer response questionnaires with descriptive quantitative analysis techniques. The analysis of validator assessments and the responses of teachers and lecturers in limited trials and extensive trials state that the e-learning developed is suitable for general use, both on campus and at school, especially in Merauke Regency.